2009
DOI: 10.1159/000232314
|View full text |Cite
|
Sign up to set email alerts
|

UFT plus Oral Folinic Acid with Alternating Oral and Intravenous Vinorelbine in Patients with Metastatic Breast Cancer Previously Treated with Anthracyclines and Taxanes

Abstract: Background: We retrospectively evaluated the activity and toxicity of uracil/tegafur (UFT) plus oral folinic acid in combination with vinorelbine (alternating intravenous (IV) on day 1 and oral on day 8) in patients with metastatic breast cancer. Patients and Methods: Treatment consisted of IV vinorelbine 25 mg/m2 on day 1 and 60 mg/m2 orally on day 8, and oral UFT 300 mg/m2 plus leucovorin 60 mg/m2 on days 1–14 with 21 days interval. All patients were refractory to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Many studies have investigated the UFT/folinic acid and vinorelbine combination, in the search for the best treatment regimen for advanced breast cancer. The most recent publication reported that patients receiving UFT and vinorelbine with the following schedule: intravenous vinorelbine 25 mg/m 2 on day 1 and 60 mg/m 2 orally on day 8, and oral UFT 300 mg/m 2 plus folinic acid 60 mg/m 2 on days 1–14 with a 21-day interval, presented a total clinical benefit of 51.6% [12]. The most common toxicities were hematological, including 12.9% of grade 3 neutropenia and 12.9% of grade 4 neutropenia; 9.7% of the patients had hand-foot syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have investigated the UFT/folinic acid and vinorelbine combination, in the search for the best treatment regimen for advanced breast cancer. The most recent publication reported that patients receiving UFT and vinorelbine with the following schedule: intravenous vinorelbine 25 mg/m 2 on day 1 and 60 mg/m 2 orally on day 8, and oral UFT 300 mg/m 2 plus folinic acid 60 mg/m 2 on days 1–14 with a 21-day interval, presented a total clinical benefit of 51.6% [12]. The most common toxicities were hematological, including 12.9% of grade 3 neutropenia and 12.9% of grade 4 neutropenia; 9.7% of the patients had hand-foot syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Dose levels were determined based on the results of the previous single-agent and combination chemotherapy trials [11,12,13,14,16,17]. The escalated dose design was based on the Fibonacci ‘3 + 3’ schedule [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation